Effect of salt stress on germination and early seedling growth of rice (Oryza sativa L.) - Hakim, Md. Abdul; Juraimi, Abdul Shukor; Begum, Mahfuza; Musa, Mohamed Hanafi; Ismail, Mohd Razi; Selamat, Ahmad (Academic Journals, 2010)
The response of twelve rice varieties against six salinity levels (0, 4, 8, 12, 16 and 20 dS m-1) were studied at germination and early seedling stages. Data were analyzed using SAS and means were separated by LSD for final germination percentage (FGP), speed of germination (SG), germination energy percentage (GE%), plumule and radical length and plumule and radical dry weight. Based on dry matter yield reduction, rice varieties were classified as tolerant (T), moderately tolerant (MT), moderately susceptible (MS) or susceptible (S). Germination was completely arrested at 20 dS m-1 salt concentration. Salinity decreased FGP, SG, GE % and led to reduction in shoot and root length and dry weight in all varieties and the magnitude of reduction increased with increasing salinity stress. Rice varieties MR211, IR20, BR40 and MR232 showed greater salt tolerance during germination (germinated at 12 dS m-1 salinity). However, MR211, MR232 and IR20 performed better based on dry matter yield reduction. The result suggested that MR211, MR232 and IR20 might be used for further study of salinity effect on growth processes and physiological consequences at advanced stage of growth, since salt tolerance of a crop at germination and early seedling stage may not correspond to that at advanced stage.